Reclamation in the Pabbi Hills, Gujrat District, Punjab - Gorrie, R. Maclagan (Indian Forester, 1937)
Thc Pabbi Hills are a deeply eroded line of low foothills in the north-west corner of Gujrat District, Punjab, with arid conditions and a precarious rainfall of a few heavy thunderstorms each monsoon. The range is 30 miles long and exhibits all stages of grazing damage between long-continued closure and persistent overgrazing. The run-off in terms of maximum peak flood has been measured by the irrigation branch during tho last 30 years for a great many individual torrents, and the records thus obtained have been correlated with catchment conditions. The results show clearly the value of constructive counter-erosion work to supplement passive protection against grazing. All historical account is given of the reclamation work which has been carried on intermittently since 1877 and is now effectively controlling run-off over 3,000 acress, suggestions for future work include stricter grazing control over the whole "reserved forest" land acquisition and eviction of graziers from land not yet reserved, "gully plugging" in torrent head waters to reduce flood peaks, improvement of natural graas crops by contour trenching and afforestation with Prosopis glandulosa and Acacia modesta; also improvement of farm cultivation by stream training and contour terracing.